ANALISIS KEMANDIRIAN DAERAH DAN DERAJAT DESENTRALISASI FISKAL DAERAH KABUPATEN SUMBAWA - Elly Karmeli; Wahyu Haryadi; M Muslimin (Pusat Riset dan Publikasi, 2022)
This research aims to analyze regional autonomy and degree of fiscal decentralization of Sumbawa District in 2015-2019. This type of research is descriptive research, which is a research that aims to determine the value of the independent variable, without connecting or making comparisons with other variables. The quantitative data used was obtained from secondary sources by collecting documents that already exist in the form of target data and the realization of regional revenue and expenditure budget of Sumbawa District in 2015-2019. Data analysis was performed using financial ratio analysis techniques. These research findings indicate that the region autonomy and degree of fiscal decentralization of Sumbawa District in 2015-2019 is still very low. The average percentage in 2015-2019 is 17.02 % or having instructive relationship patterns, while the ratio of fiscal decentralization of Sumbawa District in 2015-2019 is 10.67 % or fell in the low category. This condition illustrates that Sumbawa District rely heavily on the income that comes from outside regional revenue, such as balancing funds and other legitimate income.